Имитационное моделирование процессов в реакторе ВВЭР-1000 при регулировании мощности поглощающими стержнями - Северин, Валерий Петрович; Никулина, Елена Николаевна; Лукинова, Дарина Андреевна (НТУ "ХПИ", 2017)
Представлены математические модели реактора ВВЭР-1000 серии В-320 в относительных переменных состояния, которые описывают нейтронную кинетику реактора, тепловые процессы, изменение концентрации ксенона при регулировании мощности поглощающими стержнями, и вычислены значения параметров моделей. Проведено имитационное моделирование процессов, протекающих в реакторе ВВЭР-1000 при регулировании мощности реактора поглощающими стержнями, и получены переходные процессы, позволяющие анализировать изменения переменных состояния активной зоны реактора.

Mathematical models of WWER-1000 nuclear reactor of V-320 series are presented in the form of systems of differential equations in relative state variables. These models describe the neutron kinetics of the reactor with six groups of delayed neutrons, gradual heat release in fuel, changes in fuel temperature, fuel element envelopes and coolant, change in xenon concentration when power is regulated by absorbing rods. The values of the model parameters are calculated. Simulated modeling of the processes taking place in the WWER-1000 reactor was carried out while adjusting the reactor power with absorbing rods. Transient processes are shown that allow one to analyze changes in the variables of the state of the reactor core.
Simulation modeling of processes in the WWER-1000 reactor with power control by absorbing rods
Keywords: ядерный реактор; математическая модель; нейтронная кинетика реактора; концентрация ксенона; nuclear reactor; mathematical model; simulation modeling; power control